Expansão urbana e estruturação de bairros do Rio de Janeiro: o caso de Botafogo - Santos, Sergio Roberto Lordello dos (1981)
The study aims to describe the evolution of the ''bairro" of Botafogo as an example of the developing of Rio de Janeiro City in ''bairro" units that formed its internal structure. It brings to discussion the urban evolution of the city in general through Botafogo as a case study remarking the main elements that have structured the "bairro" and their influence in its evolution the internal structure of ''bairro de Botafogo" is then discussed through its economic, demographic, social, politic and institutional agents.